Association between periodontitis stages and self-reported diseases in a Norwegian population: the HUNT study - Ida Haukåen Stødle; Abhijit Sen; Hedda Høvik; Anders Verket; Odd Carsten Koldsland (BMC, 2023)
Abstract Background The relationships between periodontitis and non-communicable diseases (NCDs) have been investigated through several different case-definitions. The differences in methodology may have hindered the basis of comparison between these studies. The classification from the 2017 World Workshop on the Classification of Periodontal and Peri-implant Diseases and Conditions offers a unison platform that may facilitate future comparison of such research. The present study aimed to reproduce associations between periodontitis and other NCDs using the 2017 Classification, in the Trøndelag Health Study (HUNT). Material and methods The fourth HUNT-survey was carried out between 2017 and 2019. Clinical variables, blood samples and answers to questionnaires were collected from 4933 participants. Periodontal status was assessed based on the latest staging system, and its associations with NCDs were estimated by logistic regression models adjusted for potential confounders. Results Compared to no or Stage I periodontitis, participants with Stage III/IV periodontitis (radiographic bone loss exceeding 33%) were associated with cardiovascular disease, hyperglycemia in participants with diabetes and chronic obstructive pulmonary disease (COPD)/emphysema. Associations with hyperglycemia in participants with diabetes and COPD/emphysema were also observed in participants with Stage II periodontitis. The only observed association when considering never-smokers alone, was with COPD/emphysema. Conclusion Periodontitis Stage II and III/IV were associated with major NCDs. Effect sizes increased with increasing periodontitis stages, which implies greater occurrence of coincident comorbidities in patients with severe periodontitis.